A Study of Demonetization Announcement Effect on Indian Stock Market (Trinity Journal of Management, IT & Media (TJMITM), 2017)
This study examines the impact of demonetization  announcement effect on the returns of stock market & quantum of  Investment through traded value in India for a very short period of  time. The study examines the daily data of closing prices of S&P CNX Nifty Index and its traded value during pre and post  demonetization periods. This is a new aspect that has been  experimented by the existing government to eradicate black  money, counter tax-evasion and destroy counterfeit currency  from the Indian economy. The paper is basically concentrating on  the effect of this government strategy on the capital market  returns & its turnover. There is a mixed reaction on  demonetization announcement among the different stakeholders  of the economy. The present study is an attempt to understand  the reaction of Indian capital market after demonetization. A standard event study methodology has been adopted to examine  the pattern of changes that has taken place surrounding 50 days  of the announcement date.
Keywords: S&P CNX Nifty Returns; Traded value; Demonetization; Event Study; Announcement date